Association between postpartum thyroid dysfunction and thyroid antibodies and depression. Issue 6846 (18th July 1992) - Harris, B.; Othman, S.; Davies, J. A.; Weppner, G. J.; Richards, C. J.; Newcombe, R. G.; Lazarus, J. H.; Parkes, A. B.; Hall, R.; Phillips, D. I.
Abstract : OBJECTIVE--To define the relation between mood and autoimmune thyroid dysfunction during the eight months after delivery. DESIGN--Double blind comparison of the psychiatric status of women positive and negative for thyroid antibodies. Clinical examination and blood sampling for free triiodothyronine and thyroxine, thyroid stimulating hormone, and thyroid antibody concentrations at four weekly intervals. Psychiatric assessment at six, eight, 12, 20, and 28 weeks post partum. SETTING--Outpatient department of district hospital. PATIENTS--145 antibody positive women and 229 antibody negative women delivering between August 1987 and December 1989. MAIN OUTCOME MEASURES--Thyroid status. Number of cases of mental ill health by the general health questionnaire, research diagnostic criteria, Hamilton 17 item depression scale, hospital anxiety and depression scale, and Edinburgh postnatal depression scale. RESULTS--Six weeks after delivery the general health questionnaire showed 62 (43%) antibody positive women and 65 (28%) antibody negative women had mental ill health (chi 2 = 8.18, p less than 0.005). Follow up of 110 antibody positive and 132 antibody negative women showed significantly greater depression by research diagnostic criteria in antibody positive women (47%) than antibody negative women (32%) regardless of thyroid dysfunction. Antibody positive women showed higher mean scores for depression on the Hamilton (6.01 v 3.89, p = 0.0002), Edinburgh (7.45 v 5.92, p = 0.031), and hospital depression scales (4.95 v 3.79, p = 0.003). CONCLUSION--Depressive symptoms are associated with positive thyroid antibody status in the postpartum period.